2015
DOI: 10.1038/srep12073
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the functionalities of a mesocrystal via structural coupling

Abstract: In the past decades, mesocrystal, a kind of nanocrystals with specific crystallographic orientation, has drawn a lot of attention due to its intriguing functionalities. While the research community keeps searching for new mesocrystal systems, it is equally crucial to develop new approaches to tune the properties of mesocrystals. In this work, a self-organized two-dimensional mesocrystal composed of highly oriented CoFe2O4 (CFO) nano-crystals with assistance of different perovskite matrices is studied as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…The TEY signals of (Fe,Co)-L 2,3 XAS and XMCD of the RT sample at grazing incidence [ Figure 6a,b for Fe-L 2,3 and Co-L 2,3 edges, respectively] show the spectral features typically observed in the CFO films: 28,[45][46][47][48] the Fe-L 3 XMCD displays one positive (~709 eV) and two negative peaks (~708, ~710 eV) corresponding to their tetrahedral (T d ) and octahedral (O h ) site occupancies, respectively, whose spins are known to be antiparallel to each other [ Figure 6a]. These features are similar to those observed in the isostructural -Fe 2 O 3 oxide, [49][50] indicating that iron ions of the CFO film are in 3d 5 -Fe 3+ state.…”
Section: X-ray Absorption and Magnetic Circular Dichroismmentioning
confidence: 99%
“…The TEY signals of (Fe,Co)-L 2,3 XAS and XMCD of the RT sample at grazing incidence [ Figure 6a,b for Fe-L 2,3 and Co-L 2,3 edges, respectively] show the spectral features typically observed in the CFO films: 28,[45][46][47][48] the Fe-L 3 XMCD displays one positive (~709 eV) and two negative peaks (~708, ~710 eV) corresponding to their tetrahedral (T d ) and octahedral (O h ) site occupancies, respectively, whose spins are known to be antiparallel to each other [ Figure 6a]. These features are similar to those observed in the isostructural -Fe 2 O 3 oxide, [49][50] indicating that iron ions of the CFO film are in 3d 5 -Fe 3+ state.…”
Section: X-ray Absorption and Magnetic Circular Dichroismmentioning
confidence: 99%
“…On the other hand, strain is a common tool to modulate the cation redistribution of CFO. Liu et al 23 provided an approach to tune the anisotropy of CFO by varying the surrounding matrices in matrix/nanocrystal heterostructures. In that study, XMCD results directly evidenced the relation of cation distribution with strain state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In these systems, the oxide mesocrystal and matrix can establish compact connection with each other, which can strongly affect the structural and physical properties of the mesocrystal29. Thus, the selection of the matrix materials is very important as they provide the flexibility of tailoring the crystal orientations30 and physical properties of the mesocrystal. In this study, we demonstrated that in a self-assembled BFO–CFO mesocrystal, the constraints imposed by CFO matrix can provide an additional elastic energy term to stabilize the switched BFO domains since CFO is mechanically harder than BFO30.…”
Section: Resultsmentioning
confidence: 99%